eQTL Epistasis – Challenges and Computational Approaches - Huang, Yang; Wuchty, Stefan; Przytycka, Teresa M. (Frontiers in Genetics, 2013)
The determination of eQTL epistasis - a form of functional interaction between genetic loci that affect gene expression - is an important step towards the thorough understanding of gene regulation. Since gene expression has emerged as an “intermediate” molecular phenotype eQTL epistasis might help to explain the relationship between genotype and higher level organismal phenotypes such as diseases. A characteristic feature of eQTL analysis is the big number of tests required to identify associations between gene expression and genetic loci variability. This problem is aggravated, when epistatic effects between eQTLs are analyzed. In this review, we discuss recent algorithmic approaches for the detection of eQTL epistasis and highlight lessons that can be learned from current methods.